2004
DOI: 10.1590/s0102-33062004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Revisão taxonômica de Myrocarpus Allemão (Leguminosae, Papilionoideae, Sophoreae)

Abstract: RESUMO -(Revisão taxonômica de Myrocarpus Allemão (Leguminosae, Papilionoideae, Sophoreae)). Em Myrocarpus, gênero exclusivamente sul-americano, são reconhecidas cinco espécies: Myrocarpus frondosus Allemão, M. leprosus Pickel, M. venezuelensis Rudd, M. fastigiatus Allemão e M. emarginatus A.L.B. Sartori & A.M.G. Azevedo. Na delimitação das espécies são discutidos dados de morfologia, hábitats e de distribuição geográfica. A morfologia das pétalas e a ornamentação da região seminífera são caracteres relevantes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 7 publications
(12 reference statements)
0
5
0
2
Order By: Relevance
“…The short hypanthium is another shared characteristic between members of Dipterygeae. It has been described in some other groups of Papilionoideae, including the tribes Amorpheae (McMahon, ; McMahon & Hufford, ), Loteae (Prenner, ), Dalbergieae (Costa et al ., ; Filardi, Garcia & Carvalho‐Okano, ), Sophoreae (Tucker, , , ; Sartori & Tozzi, ; Filardi et al ., ) and Phaseoleae (Tucker, ) and the Lecointea clade (Mansano et al ., ). In Caesalpinioideae s.l.…”
Section: Discussionmentioning
confidence: 99%
“…The short hypanthium is another shared characteristic between members of Dipterygeae. It has been described in some other groups of Papilionoideae, including the tribes Amorpheae (McMahon, ; McMahon & Hufford, ), Loteae (Prenner, ), Dalbergieae (Costa et al ., ; Filardi, Garcia & Carvalho‐Okano, ), Sophoreae (Tucker, , , ; Sartori & Tozzi, ; Filardi et al ., ) and Phaseoleae (Tucker, ) and the Lecointea clade (Mansano et al ., ). In Caesalpinioideae s.l.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning electron (Sartori, 2000) and optical microscope studies showed hypostomatic leaflets in Myroxylon , Myrospermum and Myrocarpus . Among the 106 species assessed by Leelavathi, Ramayya & Prabhakar (1980), 31% had hypostomatic leaves, and two of these belonged to Ormosia Jacks.…”
Section: Resultsmentioning
confidence: 99%
“…Anatomical studies showed that the kidney‐shaped outline of the main vascular bundle occurred only in Myrocarpus frondosus . In a taxonomic revision (Sartori, 2000), several specimens of Myrocarpus frondosus were considered doubtful because of considerable variation in leaflet shape and size and also in flowering, calyx and petal shape. However, the data in the present study reinforced the synonymy of Myrocarpus paraguariensis with Myrocarpus frondosus proposed by Rudd (1972) as no relevant difference was found on which to base the recognition of another species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As identificações das espécies basearam-se em chaves analíticas e consultas a bibliografias específicas (Barneby 1991, Sartori & Tozzi 2004, Carvalho 2003, 2006, Ramos et al 2008, Silva & Tozzi 2012a, comparação das exsicatas em herbários e auxílio de especialistas, quando necessário.…”
Section: Introductionunclassified